Unpacking the environment-gender-time poverty nexus in Bangladesh: insights from a systematic review - Sarker, Mou Rani; Puskur, Ranjitha; Sarkar, Md Abdur Rouf (Informa UK Limited, 2025)
The climate vulnerability of Bangladesh has been extensively studied, but the impacts of climate change on time poverty remain underexplored. This systematic review adopts a systems approach to investigate the climate-gender-time poverty nexus. The study searched four databases for English primary qualitative studies published from 2000 to 2023. Out of 808 publications reviewed, 41 met the inclusion criteria. The study presents a framework for understanding environmental time poverty, demonstrating that climate change directly increases the time burden across five themes: water, energy, infrastructure, gender roles, and health. Household adaptation practices such as migration and alternative livelihoods further compound this burden. Consequently, both climate impacts and adaptation practices exacerbate time poverty, creating a cycle of increased burden. The analysis highlights that demographic, cultural, and socio-economic factors strongly mediate time poverty. It illustrates how multiple pathways such as workload, overburdening, multitasking, and trade-offs, can amplify time poverty. However, the study also recognizes that adaptation strategies can serve as pathways to enhance gender equality and empower women. For a more sustainable future, policies and programmes should prioritize reducing and recognizing unpaid work by promoting gender and climate awareness, providing access to time and labour-saving technologies, ensuring equitable access to daily necessities, fostering employment opportunities, and expanding access to finance.